Impact of endocrine disrupting chemicals and pharmaceuticals on Sertoli cell development and functions - Corpuz-Hilsabeck, Maia; Culty, Martine (Frontiers in Endocrinology, 2023)
Sertoli cells play essential roles in male reproduction, from supporting fetal testis development to nurturing male germ cells from fetal life to adulthood. Dysregulating Sertoli cell functions can have lifelong adverse effects by jeopardizing early processes such as testis organogenesis, and long-lasting processes such as spermatogenesis. Exposure to endocrine disrupting chemicals (EDCs) is recognized as contributing to the rising incidence of male reproductive disorders and decreasing sperm counts and quality in humans. Some drugs also act as endocrine disruptors by exerting off-target effects on endocrine tissues. However, the mechanisms of toxicity of these compounds on male reproduction at doses compatible with human exposure are still not fully resolved, especially in the case of mixtures, which remain understudied. This review presents first an overview of the mechanisms regulating Sertoli cell development, maintenance, and functions, and then surveys what is known on the impact of EDCs and drugs on immature Sertoli cells, including individual compounds and mixtures, and pinpointing at knowledge gaps. Performing more studies on the impact of mixtures of EDCs and drugs at all ages is crucial to fully understand the adverse outcomes these chemicals may induce on the reproductive system.